Implementation of web comic across modern website using Adobe Muse and Edge Animate / Mohd Fauzan Sarif - Sarif, Mohd Fauzan (2013)
Website programming is something difficult and not every person try to understand what is all about. If necessary, comic artist can choose another platform like website as a platform of publishing their own comic. This thesis is about implementation of interactive web comic toward modern design using Adobe Muse and Edge Animate. This methods is suitable for person who doesn't know well about website programming. This is the time for comic artist to have their own website rather using blogging site as an alternative approach. The challenging of comic world today is how comic maker find a new approach to bring a new spirit and increase the reader satisfaction when read a comic. Additional criteria to enhance a comic is relevan on this era. Comic maker sometimes need a new effective approach toward comic development and reader sometimes need a special experience when read a comic. Not just a still comic, but maybe has a animate picture, music, interact button and etc. That criteria forces comic maker to develop something useful on their comic, absolutely for increase the reader satisfaction. The colourful of comic industry can we describe on creative tools software and how comic maker play around with that tools. Comic today give a lot of experience like motion, animate, and interactive. Interactive is just necessary for comic but it is useful to fulfill the reader satisfaction. So, it is really depended on comic maker what kind of method they want to do.